Pētera Ķiķaukas runa Akadēmiskās kopas sanāksmē 1953. gada 3. oktobrī - Ķiķauka, Pēteris (My University, 1953)
Prof. dr. philol. Pētera Ķiķaukas runa par godu Latvijas Universitātes 34 jubilejai. Runa nolasīta Akadēmiskās kopas sanāksmē Y.M.C.A. (Young Men’s Christian Association) telpās Kanādā. Runa ir vēstures avots par trimdas latviešu dzīvi.

Prof. dr. philol. Pēteris Ķiķaukas speech on the occasion of the 34th anniversary of the University of Latvia. The speech was delivered at the Academic Group meeting at the Y.M.C.A. (Young Men's Christian Association) in Canada. The speech is a historical source on Latvian life in exile.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History; Latvijas Universitāte; Augstākā izglītība; Zinātņu vēsture; Trimdas latvieši; Latvijas Universitātes mācībspēki; The University of Latvia; Higher education; History of Science; Exile Latvians; Teaching staff of the University of Latvia